Strabismic Adults' Experiences of Psychosocial Influence of Strabismus-A Qualitative Study - Anna Mason RN, MHS; Katja Joronen RN, PhD; Laura Lindberg MD, PhD; Marika Kajander Master of Arts (Psychology); Nina Fagerholm RN, PhD; Anja Rantanen RN, PhD (SAGE Publishing, 2024)
Introduction Strabismus influences health-related quality of life. Individuals may have functional and psychosocial consequences of strabismus that impact their well-being. As strabismus is prevalent in all age groups, patients are seen in varied specialties in healthcare organizations. Therefore, healthcare professionals need to be aware of the psychosocial consequences when caring for strabismic individuals. Objective To describe strabismic adults' experiences of the psychosocial influence of strabismus. Methods Twelve strabismic adults participated in face-to-face or online semistructured individual interviews to share their experiences of the psychosocial influence of strabismus. The participants were selected purposefully. The data were analyzed using inductive content analysis. Results The participating adults described challenges with social environments, which showed stress in social situations and pressure in interactions. Strabismic adults had experienced staring from others, avoided social situations, and were uncomfortable with photography. They hid their strabismus, avoided eye contact, and struggled with intimate relationships. They also expressed struggles with mental well-being, which were emotional and psychological burdens. The adults described feeling negative emotions, worry, and irritation due to their condition. Struggles with self-confidence, difficulties with acceptance, negative thoughts about their appearance, experiences of bullying, and dealing with being different were described. Conclusion Strabismic adults experience psychosocial consequences of strabismus, influencing their psychosocial health-related quality of life. Further studies should focus on how healthcare professionals could support strabismic individuals' psychosocial well-being.